A general concept for highly efficient covalent laser patterning of graphene based on silver carboxylates - Wei, Tao; Liu, Xin; Al-Fogra, Sabrin; Bachmann, Julien; Hauke, Frank; Hirsch, Andreas (Chemical Communications, 2021)
Three novel types of spatially resolved graphene architectures GA, GB, and GC respectively bearing CH3-, C6H5- and C3F7 groups are efficiently constructed by newly developed laser-writing concepts using silver carboxylates as corresponding photosensitizers. These 2D-structured samples are unequivocally characterized by Raman spectroscopy and SEM-EDS. This journal is
CRIS-Team Scopus Importer:2021-05-21

A straightforward reductive approach for the deoxygenation, activation and functionalization of ultrashort single-walled carbon nanotubes - Bao, Lipiao; Martin, Oliver; Wei, Tao; Perez-Ojeda Rodriguez, Maria Eugenia; Hauke, Frank; Hirsch, Andreas (Carbon, 2021)
We report here a straightforward reductive approach for the deoxygenation, activation and functionalization of ultrashort single-walled carbon nanotubes (us-SWCNTs). Us-SWCNTs with lengths of only 20–50 nm were prepared by the low-temperature oxidative-cutting process which inevitably introduced oxygen-containing groups onto the nanotube framework. For the subsequent deoxygenation, six routes have been investigated and the reduction with potassium is the optimal one that can efficiently remove the oxidized groups and consequently recover the inherent structures and properties of us-SWCNTs. This reductive approach permits at the same time very efficient activation of the chemically inert nanotubes by generating the intermediate us-SWCNTn- carbanions. Subsequent quenching these negative charges on the nanotube backbone using electrophiles affords very efficient covalent binding of distinct building blocks as porphyrin, phenyl or hexyl moieties onto us-SWCNTs. Additionally, the Birch-type reductive approach was also performed to realize the first hydrogenation of us-SWCNTs by using water as proton source and lithium as reducing agent.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Activation; Carbon nanotube; Functionalization; High degree of functionalization; Reduction; Ultrashort carbon nanotube

Chemical Vapor Deposition Strategy of Fe-N-C Nanotubes for the Oxygen Evolution Reaction - Liu, Xin; Wei, Tao; Englhard, Jonas; Barr, Maissa; Hirsch, Andreas; Bachmann, Julien (Advanced Science, 2025)
The conversion of metal-nitrogen-carbon (M-N-C) nanoparticles derived from conventional metal-organic frameworks (MOFs) into self-supporting and well-defined metal-nitrogen-carbon (M-N-C) superstructures is essential for various functional applications but remains a significant challenge. In this study, a versatile chemical vapor deposition (CVD) strategy is developed for solvent-free synthesis of self-supporting carbonaceous nanotubes doped with metal and nitrogen (MNCT). The stable carbonaceous nanotubes doped with Fe and N (FeNCT) fabricated here exhibit excellent electrocatalytic performances for the oxygen evolution reaction (OER) and outperform the carbonaceous film doped with Fe and N grown on carbon foil directly (FeNC/CF), which demonstrates the advantages of the superstructure of FeNCT. This strategy also provides a way to tailor the metal-nitrogen-carbon nanotubes (MNCT) catalyst according to the feature of the reactor and exhibits many advantages, such as wide applicability and facile scalability.
CRIS-Team Scopus Importer:2025-04-25
Keywords: atomic layer deposition; carbon-based materials; chemical vapor deposition; electrocatalysis; nanotube; oxygen evolution reaction; precise chemistry

Covalent Inter-Carbon-Allotrope Architectures Consisting of the Endohedral Fullerene Sc3N@C80and Single-Walled Carbon Nanotubes - Wei, Tao; Martin, Oliver; Chen, Muqing; Yang, Shangfeng; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2019)
Using a reductive sidewall functionalization concept, we prepared for the first time a covalent inter-carbon-allotrope hybrid consisting of single-walled carbon nanotubes (SWCNTs) and the endohedral fullerene Sc 3 N@C 80 . The new compound type was characterized through a variety of techniques including absorption spectroscopy, Raman spectroscopy, TG-MS, TG-GC-MS, and MALDI-TOF MS. HRTEM investigations were carried out to visualize this highly integrated architecture.
CRIS-Team Scopus Importer:2019-06-04
Keywords: carbon nanotubes; endohedral metallofullerene; HRTEM; hybrid materials; Raman spectroscopy

Covalent Inter-Synthetic-Carbon-Allotrope Hybrids - Wei, Tao; Hauke, Frank; Hirsch, Andreas (Accounts of Chemical Research, 2019)
Inter-synthetic-carbon-allotrope (SCA) architectures are constructed by hybridizing different types of carbon allotropes such as OD-fullerene, 1D-carbon nanotubes (CNTs), and 2D-graphene. Also hybridizations of different fullerene families (e.g., empty fullerene, heterofullerenes, and endohedral fullerenes as well as their isomers) are considered as inter-SCA architectures and represent an emerging class of nanofunctional materials. Such highly integrated hybrids are quite promising, since they hold the potential of combining unique properties of each building block. For instance, hybridization of 2D-graphene, a synthetic carbon allotrope with outstanding chemical/physical properties, with OD-fullerenes leads to materials with both outstanding solid state properties (e.g., electron mobility, flexibility, transparency, and mechanical stability) and distinct molecular properties (spatially resolved and tailor-made exohedral cage functionalization and endohedral guest encapsulation). Therefore, such integrated hybrids have potential as multifunctional nanocarbon materials applicable, for example, in energy storage, electronic devices, solar cells, or advanced sensors. Recognizing these significant advantages, a series of methods and techniques has been developed to synthesize such integrated hybrids. Based on in-depth understanding of fullerene chemistry, interfullerene hybrids where multiple fullerenes are linked together have been synthesized and fully characterized. However, due to the difficulty in functionalizing graphene or CNTs as a result of their poor dispersibility and weak reactivity the corresponding hybrids including these macromolecular forms are less explored. Furthermore, few approaches toward such systems reported so far inevitably involve some drawbacks such as low degree of addition and low production ability.
CRIS-Team WoS Importer:2019-09-13

Direct Laser Writing on Graphene with Unprecedented Efficiency of Covalent Two-Dimensional Functionalization - Wei, Tao; Al-Fogra, Sabrin; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2020)
Laser writing as a simple and straightforward method for covalent 2D patterning of graphene remains challenging. Here, we report a facile and efficient approach for a laser-induced 2D patterning of graphene utilizing silver trifluoroacetate, providing an unprecedented high degree of functionalization. The use of laser-triggered photolysis of silver trifluoroacetate to generate trifluoromethyl radicals, confined only to the laser-irradiated region, leads to the selective reaction of graphene, thereby completing direct laser writing on graphene toward a spatially resolved 2D-patterned architecture. This highly 2D-functionalized graphene is completely reversible. Furthermore, a more complex patterned graphene hybrid architecture was constructed, taking advantage of the simultaneously produced/patterned silver nanoparticles during the laser-writing process. Considering the simplicity of this approach and its ability to provide high degrees of functionalization, the prerequisite of 2D patterning of other 2D materials based on this method is provided.
CRIS-Team Scopus Importer:2021-01-15

Evolution of Graphene Patterning: From Dimension Regulation to Molecular Engineering - Wei, Tao; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2021)
The realization that nanostructured graphene featuring nanoscale width can confine electrons to open its bandgap has aroused scientists' attention to the regulation of graphene structures, where the concept of graphene patterns emerged. Exploring various effective methods for creating graphene patterns has led to the birth of a new field termed graphene patterning, which has evolved into the most vigorous and intriguing branch of graphene research during the past decade. The efforts in this field have resulted in the development of numerous strategies to structure graphene, affording a variety of graphene patterns with tailored shapes and sizes. The established patterning approaches combined with graphene chemistry yields a novel chemical patterning route via molecular engineering, which opens up a new era in graphene research. In this review, the currently developed graphene patterning strategies is systematically outlined, with emphasis on the chemical patterning. In addition to introducing the basic concepts and the important progress of traditional methods, which are generally categorized into top-down, bottom-up technologies, an exhaustive review of established protocols for emerging chemical patterning is presented. At the end, an outlook for future development and challenges is proposed.
CRIS-Team WoS Importer:2021-10-08

Highly Efficient and Reversible Covalent Patterning of Graphene: 2D-Management of Chemical Information - Wei, Tao; Kohring, Malte; Chen, Muqing; Yang, Shangfeng; Weber, Heiko B.; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2020)
Patterned graphene-functionalization with a tunable degree of functionalization can tailor the properties of graphene. Here, we present a new reductive functionalization approach combined with lithography rendering patterned graphene-functionalization easily accessible. Two types of covalent patterning of graphene were prepared and their structures were unambiguously characterized by statistical Raman spectroscopy together with scanning electron microscopy/energy-dispersive X-ray spectroscopy (SEM-EDS). The reversible defunctionalization processes, as revealed by temperature-dependent Raman spectroscopy, enable the possibility to accurately modulate the degree of functionalization by annealing. This allows for the management of chemical information through complete write/store/erase cycles. Based on our strategy, controllable and efficient patterning graphene-functionalization is no longer a challenge and facilitates the development of graphene-based devices.
CRIS-Team WoS Importer:2020-02-11

Laser-Driven Modular Precision Chemistry of Graphene Using λ3-Iodanes - Gerein, Kevin; Unmu Dzujah, Diyan; Yu, Hongde; Hauke, Frank; Heine, Thomas; Hirsch, Andreas; Wei, Tao (Angewandte Chemie International Edition, 2024)
The emerging laser writing represents an efficient and promising strategy for covalent two dimensional (2D)-patterning of graphene yet remains a challenging task due to the lack of applicable reagents. Here, we report a versatile approach for covalent laser patterning of graphene using a family of trivalent organic iodine compounds as effective reagents, allowing for the engraving of a library of functionalities onto the graphene surface. The relatively weak iodine-centered bonds within these compounds can readily undergo laser-induced cleavage to in situ generate radicals localized to the irradiated regions for graphene binding, thus completing the covalent 2D-structuring of this 2D-film. The tailor-made attachment of distinct functional moieties with varying electrical properties as well as their thermally reversible binding manner enables programming the surface properties of graphene. With this delicate strategy the bottleneck of a limited scope of functional groups patterned onto the graphene surface upon laser writing is tackled.
CRIS-Team Scopus Importer:2024-11-15
Keywords: covalent functionalization; graphene; graphene patterning; laser chemistry; Raman spectroscopy

Modular Covalent Graphene Functionalization with C60 and the Endohedral Fullerene Sc3N@C80: A Facile Entry to Synthetic-Carbon-Allotrope Hybrids - Wei, Tao; Martin, Oliver; Yang, Shangfeng; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2019)

Molecular embroidering of graphene - Wei, Tao; Kohring, Malte; Weber, Heiko B.; Hauke, Frank; Hirsch, Andreas (Nature Communications, 2021)

Molecular Stacking on Graphene - Wei, Tao; Liu, Xin; Kohring, Malte; Al-Fogra, Sabrin; Moritz, Michael; Hemmeter, Daniel; Paap, Ulrike; Papp, Christian; Steinrück, Hans-Peter; Bachmann, Julien; Weber, Heiko B.; Hauke, Frank; et al. (Angewandte Chemie International Edition, 2022)
The sequentialverticalpolyfunctionalizationof 2D addend-patternedgrapheneis still elusive.Here,we reporta practicalrealizationof this goalvia a “molecularbuildingblocks”approach,whichis basedon a combinationof alithography-assistedreductivefunctionalizationapproachanda post-functionalizationstepto sequentiallyandcontrollablylink the molecularbuildingblocksethylpyridine,cis-dichlorobis(2,2’-bipyridyl)ruthenium,and triphenyl-phosphine(4-methylbenzenethiol,respectively)on selectedlatticeregionsof a graphenematrix.The assembled2Dhetero-architecturesare unambiguouslycharacterizedby variousspectroscopicand microscopicmeasurements,revealingthe stepwisestackingof the molecularbuildingblockson the graphenesurface.Our methodovercomesthe currentlimitationof a one-layer-onlybindingto the graphenesurfaceand opensthe doorfor a verticalgrowthin the z-directio

Precision Chemistry of Metallofullerenes and Graphene: Recent Advances - Chang, Xueyi; Chen, Muqing; Wei, Tao (ChemPlusChem, 2024)
Precision chemistry of synthetic carbon allotropes including fullerene and graphene, characterized by a well-controlled and spatially resolved addends bonding, has received widespread attention owing to its capability to tailor their physicochemical properties for high-end applications. In the context of fullerene, particularly endohedral metallofullerenes (EMFs), precision chemistry emphasizes the regioselective binding of a specific number of moieties to the fullerene cage. In the case of graphene, precision chemistry focuses on achieving precise patterning and tailored modifications. Inspired by their intriguing advantages, the precision chemistry of these two members has witnessed rapid advancements. While existing reviews have outlined advancements in the precision chemistry of EMFs and graphene, this review uniquely concentrates on the most recent progress. Finally, the prospects in this field, with a special focus on the potential for creating functional materials through strategically patterned binding of fullerene and graphene networks are envisioned.
CRIS-Team Scopus Importer:2024-08-30
Keywords: Electrosynthesis; Endohedral metallofullerene; Graphene; Graphene patterning; Laser-writing; Precision chemistry

Recent Advances in Graphene Patterning - Wei, Tao; Bao, Lipiao; Hauke, Frank; Hirsch, Andreas (ChemPlusChem, 2020)
As an emerging field of research, graphene patterning has received considerable attention because of its ability to tailor the structure of graphene and the respective properties, aiming at practical applications such as electronic devices, catalysts, and sensors. Recent efforts in this field have led to the development of a variety of different approaches to pattern graphene sheets, providing a multitude of graphene patterns with different shapes and sizes. These established patterning techniques in combination with graphene chemistry have paved the road towards highly attractive chemical patterning approaches, establishing a very promising and vigorously developing research topic. In this review, an overview of commonly used strategies is presented that are categorized into top-down and bottom-up routes for graphene patterning, focusing mainly on new advances. Other than the introduction of basic concepts of each method, the advantages/disadvantages are compared as well. In addition, for the first time, an overview of chemical patterning techniques is outlined. At the end, the challenges and future perspectives in the field are envisioned.
CRIS-Team Scopus Importer:2020-08-14
Keywords: covalent functionalization; graphene; lithography; nanostructures; patterning

Spatially resolved fluoroalkylation and alkylation of graphene by direct laser writing - Al-Fogra, Sabrin; Rohde, Reina Sofia; Speck, Marcus; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Chemical Communications (London), 2024)

Spatially Resolved Janus Patterning of Graphene by Direct Laser Writing - Al-Fogra, Sabrin; Yang, Bowen; Jurkiewicz, Lisa; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Journal of the American Chemical Society, 2022)
Covalently patterned Janus-functionalized graphene featuring a spatially defined asymmetric bifacial addend binding motif remains a challenging synthetic target. Here, a facile and universal laser writing approach for a one-step covalent Janus patterning of graphene is reported, leading to the formation of up to now elusive graphene architectures, solely consisting of antaratopically functionalized superlattices. The structurally defined covalent functionalization procedure is based on laser-triggered concurrent photolysis of two different photosensitizers situated on both sides of the graphene plane, generating radicals and subsequent addend binding in the laser-irradiated areas only. Careful structure analysis was performed by Raman spectroscopy and Kelvin probe force microscopy. In terms of the advantages of our newly established concept, including a simple/easy-to-operate patterning procedure, arbitrary pattern availability, and a high degree of addend binding, an easy access to tailor-designed Janus-functionalized graphene devices with spatially resolved functional entities can be envisaged.
CRIS-Team Scopus Importer:2022-11-04

Synergistic Combination of Reductive Covalent Functionalization and Atomic Layer Deposition—Towards Spatially Defined Graphene-Organic-Inorganic Heterostructures - Liu, Xin; Yang, Bowen; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; Bachmann, Julien; Hauke, Frank; Hirsch, Andreas; Wei, Tao (Angewandte Chemie International Edition, 2023)
Three-dimensionally (3D) well-ordered and highly integrated graphene hybrid architectures are considered to be next-generation multifunctional graphene materials but still remain elusive. Here, we report the first realization of unprecedented 3D-patterned graphene nano-ensembles composed of a graphene monolayer, a tailor-made structured organophenyl layer, and three metal oxide films, providing the first example of such a hybrid nano-architecture. These spatially resolved and hierarchically structured quinary hybrids are generated via a two-dimensional (2D)-functionalization-mediated atomic layer deposition growth process, involving an initial lateral molecular programming of the graphene lattice via lithography-assisted 2D functionalization and a subsequent stepwise molecular assembly in these regions in the z-direction. Our breakthrough lays the foundation for the construction of emerging 3D-patterned graphene heterostructures.
CRIS-Team Scopus Importer:2023-10-27
Keywords: 3D Patterning; Atomic Layer Deposition; Graphene Chemistry; Heteroarchitectures; Molecular Assembly

The first molecular dumbbell consisting of an endohedral Sc3N@C80 and an empty C60-fullerene building block - Wei, Tao; Perez-Ojeda Rodriguez, Maria Eugenia; Hirsch, Andreas (Chemical Communications, 2017)